KARAKTERISASI BAKSO KERING KAYA PROTEIN DARI â€œMARINE BEEFâ€ DENGAN SUBSTITUSI TEPUNG SUWEG - Widodo, Richardus; Susanti Panjaitan, Tiurma Wiliana; Yuwono, Istantyo (Heuristic, 2015)
Marine beef is a meat product that has been fat dissolved so that the protein is a major part of the product. Marine beef dry form solid and hydrophilic, has a different performance from the base ingredients, but still contains nutrients according to the characteristics of the original. Weakness marine beef products is shaped in the form of flour so it does not allow for direct consumption. Suweg addition of flour mixture and emulsifier in the manufacturing process can serve as a regulator of the water content, hardness and adhesion to produce a final product that is more compact and high taste. This study aims to determine how optimal levels suweg flour and Na-CMC can be added to marine beef in order to obtain dry products based marine beef with the physical properties, the speed of rehydration and sensory properties that aroma, flavor and texture is good and acceptable to consumers. Treatment of dry meatballs are rich in protein from marine beef with the addition of flour suweg 15% and 1% Na-CMC is the best treatment with the shortest rehidrated pace with time 130 seconds at a temperature of boiling water and the scent of the most preferred by the panelists organoleptic test.Key word: marine beef, protein rich meatballs, suweg, Na-CMC